Perceived social support and prenatal wellbeing; The mediating effects of loneliness and repetitive negative thinking on anxiety and depression during the COVID-19 pandemic. Issue 3 (May 2022) - Harrison, Virginia; Moulds, Michelle L.; Jones, Katie
Abstract: Problem: Prenatal depression and anxiety are linked to poor maternal and infant outcomes. We need to understand predictors of poor mental health to identify at-risk women, and targets for support. Background: Previous research has demonstrated a relationship between low levels of perceived social support, and depression and anxiety in pregnant women. However, there is a lack of research into the factors that may mediate this relationship. Aim: As social distancing measures (e.g., lockdown) are likely to negatively affect women's perceived support in the prenatal period, we investigated the relationship between perceived social support and both anxiety and depression in UK-based pregnant women during the COVID-19 pandemic. Further, we examined two potential mediators that may contribute to psychological symptoms: repetitive negative thinking and loneliness. Methods: We administered a battery of online measures to a sample of pregnant women ( N  = 205) between May-June 2020, during the first peak of the pandemic in the UK, when perceived social support was likely to be low. Results: Consistent with predictions, perceived social support was significantly negatively related to depression, anxiety, loneliness and repetitive negative thinking. Furthermore, repetitive negative thinking and loneliness mediated the relationship between perceived social support and both depression and anxiety. Moreover, perceived social support and loneliness were associated with specific types of online behaviours. Conclusions: Taken together, the findings shed light on the processes through which social support may exert its effects on depression and anxiety and highlight potential therapeutic targets for interventions which aim to prevent and treat mood disorders in perinatal cohorts.